Economic Impact of Government Expenditure on Economic Growth of Nepal - Kharel, Khom Raj; Adhikari, Dipak Bahadur (Interdisciplinary Journal of Management and Social Sciences, 2021)
This paper examines the relations of government expenditure and economic growth of Nepal over the period of 1990-2019.The government expenditure of Nepal has been significantly increasing during the study period. The pattern of government spending of Nepal seems to be focused on regular expenditure and widening the budget deficit of Nepal each and every years. The track of capacity of government expenditure utilization has mostly found less efficiency which has historical tendency of Nepalese government. As per size of economy expanding, the gap of fiscal deficit has been expanding in Nepal. The objective of this study is to analyze the impact of government expenditure on economic growth of Nepal by using simple and multiple linear regression models. Descriptive and analytical research design has been used by using secondary data. The finding of the study shows that there is significant/insignificant impact of government spending on economic growth of Nepal during the study periods and addresses to be focused on increase the mobilization of capital expenditure for the expansion of development activities with rational manner of the country.